2012
DOI: 10.1002/pro.2050
|View full text |Cite
|
Sign up to set email alerts
|

Acyl carrier protein structural classification and normal mode analysis

Abstract: All acyl carrier protein primary and tertiary structures were gathered into the ThYme database. They are classified into 16 families by amino acid sequence similarity, with members of the different families having sequences with statistically highly significant differences. These classifications are supported by tertiary structure superposition analysis. Tertiary structures from a number of families are very similar, suggesting that these families may come from a single distant ancestor. Normal vibrational mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…However, Cr-cACP is unable to complement an EcACP knockout strain, suggesting that it cannot interact with all endogenous FAS enzymes, similar to spinach ACP (De Lay and Cronan 2007). The phylogeny of ACPs (Figure S2),(Cantu et al 2012b) shows –surprisingly- distinct families, even within the previously identified ACP1 family (Cantu et al 2012b), suggesting that the match between ACP and partner protein also depends on the evolutionary origin of the ACP itself.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, Cr-cACP is unable to complement an EcACP knockout strain, suggesting that it cannot interact with all endogenous FAS enzymes, similar to spinach ACP (De Lay and Cronan 2007). The phylogeny of ACPs (Figure S2),(Cantu et al 2012b) shows –surprisingly- distinct families, even within the previously identified ACP1 family (Cantu et al 2012b), suggesting that the match between ACP and partner protein also depends on the evolutionary origin of the ACP itself.…”
Section: Discussionmentioning
confidence: 83%
“…Second, Predalgo (Tardif et al 2012) (currently the only targeting prediction tool for algae) predicts mitochondrial targeting for ACP1 and chloroplastic targeting for ACP2. Third, a phylogenetic tree of ACPs shows at least 16 families (Cantu et al 2012b) (Figure S2A) and subfamilies in FAS ACPs (Figure S2B), including the two C. reinhardtii ACPs: ACP1 clustering with mitochondrial ACPs and ACP2 with chloroplastic ACPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(68) The best correlation between the experimental and theoretical B-factors was obtained by systematically changing the cutoff distance (ranging from 15–21 Å) and distance weights (ranging from 0–3) for interactions between Cα atoms, Figure S1. (69) The cut-off distance and distance weight values were changed and their corresponding Pearson's correlation coefficient values were recorded. Since the wild-type FPs are composed of multiple chains that are structurally similar, only chain A for each of them was used in these studies.…”
Section: Methodsmentioning
confidence: 99%
“…In some structures an additional short helix (helix III) is found in the second loop depends on its helix-loop equilibrium conformations (Sharma et al, 2006; Cantu et al, 2012). The longer helix-I is positioned anti-parallel to helix II and helix IV, while helix I and helix IV are arranged at a small angle relative to each other (Figure 16-A).…”
Section: Structures and Catalytic Mechanisms Of Pks Domainsmentioning
confidence: 99%